Policy Review of the Effectiveness of the Submarine Technology Transfer Roadmap between Indonesia and South Korea - Bila, Tamarell Vimy Salsa; Widodo, Widodo; Yulianto, Bayu Asih (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2023)
Indonesia is a country with enormous water areas with maritime security threats that require high security in their territorial waters including by using submarines, but the number of fleets is not optimal yet because Indonesia is required to have 12 submarines to protect their waters from threats of law violations. Indonesia took steps to build a strong defense posture by procuring submarines technology transfer cooperation with South Korea, this decision was made by Indonesia because of their limited knowledge and ability to design and produce submarines. This study is about a policy review of the effectiveness of the submarine technology transfer roadmap between PT PAL Indonesia and DSME Korea. This study aims to analyze the policy effectiveness of submarine technology transfer policies within the framework of Indonesia’s maritime defense and security. Data obtained from interviews and literature were then analyzed using qualitative analysis methods. The research’s results show first the batch submarine technology transfer policy had been implemented ineffective in supporting Indonesia’s ability to produce its submarines, and there was a gap between the target to be achieved and the technology transfer knowledge that had been obtained, the effectiveness of technology transfer could be increased by improvements in the next cooperation contract to maximize the quality of the submarine. This research concludes that the knowledge of the submarine transfer of technology in the firstbatch is ineffective in supporting the ability to produce submarines, it is necessary to continue technology transfer to the second batch to support Indonesia’s target in the ability to build its submarines with still consider the evaluation of the 1st batch to improvements in the next batch of transfer technology and also engage the educational institution, Indonesia Defense University as a knowledge base thus facilitate better output in future technology transfer cooperation.